ANALYSIS OF CONCEPT, IMPLEMENTATION AND IMPACT ON TRAINING NEEDS ASSESSMENT FOR APPARENTS IN PATTONDON VILLAGE, MAIWA DISTRICT, ENREKANG REGENCY - nasrullah nasrullah; Muchran Muchran (Universitas Muhammadiyah Makassar, 2021)
This study aims to find out how the concepts of Training Neds Assessment (TNA), how to implement Training Needs Assessment (TNA), and the impact of Training Needs Assessment (TNA) in developing the quality of officials in Pattondon Salu Village, Maiwa District, Enrekamg Regency. The sample in this study were 11 informants and the technique used was qualitative analysis conducted at the time of data collection and after data collection was completed. The data analysis activity of this research was carried out interactively and took place continuously to complete through several steps in a systematic manner, namely data collection, data reduction, data display. The results showed that the application of the Training Needs Assessment concept that could properly improve the work ability of Pattondon Salu village officials and the Implementation of Training Needs Assessment in Pattondon Salu village had a positive impact on the ability of village officials to work so that the performance of village officials was better than before training